Architecture And Politics (Study of Tarekat Preferences in the 2018 Gubernatorial Election) - Muhammad Faisal Hamdani (Budapest International Research and Critics University, 2022)
This study aims to find out the understanding of tarekat mursyids and their preferences / tendencies towards politics and participating in it, including their support for the 2018 governor election. This study uses a qualitative approach by interviewing respondents who are tarekat murshids who are always obeyed by students. The findings are enriched with literature, books, research results and thoughts of experts in related fields. The results show that there are mursyid tarekat in North Sumatra that allow them to enter politics for the greater benefit of the people (Syeikh Sofwan Babussalam), to uphold or magnify the word of Allah (Syeikh Sabban Rajagukguk) and to uphold justice, prosper the people and create prosperity. people (Syeikh Nazaruddin Brayan) and even Jabal Qubis Founder Sheikh Amir Damsar Syarif founded the Jabal Nur Indonesia Party although it did not qualify in 2002. The results of this study are reinforced by the results of Martin Van Bruinessen's research which says that in the history of Indonesia, it turns out that some tarekat mursyids and their members are involved in practical politics. They opposed the colonial movement such as Sheikh Yusuf al-Makkassari, Haji Marzuki Banten, the Naqsabandiyah-Qadiriyah caliph, Guru Bangkol in Lombok, Kasan Mukmin Sidoarjo, Naqsabandiyah affiliate.